Wages: A Systematic Literature Review And Bibliometric Analysis - Raisa Rahma, Deshinta; Sopiah, Sopiah (CV RIFAINSTITUT, 2023)
The aims of this research is to explore the topic of a wage. The literature analyzes from 31 articles from two database Taylor & Francis and Scopus which taken from Publish or Perish during the period 2017-2022, analyze with blibliometric and screening using PRISMA method to gain 31 articles. The outcome of the review indicated 127 authors from co-authorship data, four new keywords overlay from co-occurrence (employment, automation, job stress, and corporate innovation). The top 3 citations narrate about gender wage gap, minimum wage, and wage policy. This literature review can be used for a guidance for the next researcher regarding labor wage and the connection with other keywords that appropriate.